2012
DOI: 10.3917/rsg.258.0069
|View full text |Cite
|
Sign up to set email alerts
|

Comment résister à l'effet de normalisation : le défi des banques coopératives

Abstract: Distribution électronique Cairn.info pour Direction et Gestion. © Direction et Gestion. Tous droits réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit, est interdite sauf a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 7 publications
0
8
2
Order By: Relevance
“…Moreover, the standard deviation of these indicators is higher in cooperative banks, which indicates a larger variability of returns during the period. Contrary to what has been noticed above, such a result is consistent with the conclusions of Ory et al (2012). A negative way to analyze would be to conclude that cooperative banks 27 For the OECD in 2012: no country in the black list, 23 in grey list; 60 opaque territories list mentioned by the Tax Justice Network (TJN), which is also used by the CCFD (Comité Catholique contre la Faim et pour le Développement); 53 territories list for the CPO (Conseil des prélèvements obligatoires).…”
Section: Business Model: the Risk Takingcontrasting
confidence: 57%
See 4 more Smart Citations
“…Moreover, the standard deviation of these indicators is higher in cooperative banks, which indicates a larger variability of returns during the period. Contrary to what has been noticed above, such a result is consistent with the conclusions of Ory et al (2012). A negative way to analyze would be to conclude that cooperative banks 27 For the OECD in 2012: no country in the black list, 23 in grey list; 60 opaque territories list mentioned by the Tax Justice Network (TJN), which is also used by the CCFD (Comité Catholique contre la Faim et pour le Développement); 53 territories list for the CPO (Conseil des prélèvements obligatoires).…”
Section: Business Model: the Risk Takingcontrasting
confidence: 57%
“…These results do not confirm the trend pointed out by Ory et al (2012) up to 2010, which indicated a greater hybridization of the activities of cooperative banks, and a behavior and a volatility more and more close to what can be see in capitalist banks.…”
Section: Business Model: the Risk Takingcontrasting
confidence: 55%
See 3 more Smart Citations